Impact of Combat Experiences on Veteran Students in Adult Learning Environments: Two Research Perspectives - Sarah Jane Fishback; Kevin P. Shea; Maria L. Clark (Adult Education Research Conference, 2014)
Multiple combat tours have impacts on combat veteran students performance in the adult education classroom. This paper reports the results from research that details challenges such students face.